Programa de enseñanza y su incidencia en la iniciación del estilo libre en los alumnos de los séptimos grados de educación general básica de la escuela Ovidio Decroly del cantón Catamayo, periodo académico: 2012 - 2013 - Paladines Tene, Edgar Alfredo (2014)
This thesis entitled "EDUCATION AND ITS IMPACT ON THE INITIATION OF FREESTYLE IN SEVENTH GRADE STUDENTS OF GENERAL EDUCATION BASIC SCHOOL THE CANTON OVIDIO DECROLY CATAMAYO, ACADEMIC PERIOD: 2012 - 2013" By practicing freestyle swimming strengthens the improvement in the following areas: physical, motor, psychological and social; was conducted with the purpose of generating a EDUCATION AND ITS IMPACT ON THE INITIATION OF FREESTYLE IN THE SEVENTH YEAR STUDENTS OF BASIC SCHOOL OVIDIO DECROLY CATAMAYO, canton, 2013 "for the improvement of this problem. The objectives have been tested general purpose design a program of education and its impact on the initiation of freestyle swimming in seventh grade children basic general education school in Canton Catamayo Decroly Ovid. Were met by the specific objectives determine the degree of interest of the students in the seventh grade of basic education school in Ovid Decroly learn freestyle swimming; Instruct students in the seventh grade general basic education school Ovid Decroly practice freestyle swimming and students to establish conditions and have interests them, they can start in competitive swimming. Research techniques such as questionnaire was used; The Learning Program; observation; Transfer and Survey. The methodology used was through the scientific method, inductive method Deductive Method and Analytical Method - Synthetics. Finally clear and relevant results are obtained among the most important we have 21% of students say they would support the development of swimming within the institution with guides; 21% would support the development of swimming within the institution trials and 79% say they would support the development of swimming within the institution with projects because we enjoy swimming and would like to develop a project in this discipline and 100% teacher said that if he would attract the teaching of initiation of swimming in the institution Decroly Ovid.